ILUSTRASI VINYET SHIO SEBAGAI BERKARYA SENI INSPIRASI BATIK TULIS KONTEMPORER - Riskhana, Riskhana; Syakir, Syakir (Universitas Negeri Semarang, 2021)
The background for making Contemporary Batik Tulis is inspired by the animal symbol in the Chinese Zodiac / Shio as the main subject / figure by combining ornate images that have high decorative elements which are commonly called vignette illustrations as the second subject. In this study project the author is interested in visually raising twelve animal symbols in the Chinese Zodiac / Shio by applying them in a contemporary batik tulis work. On this basis, the purpose of this study project is to introduce and preserve a tradition of Chinese society that has existed for a long time and is familiar in Indonesian society, by visualizing through the art of Batik Tulis which is a culture in Indonesia. This study project includes the process of gathering ideas and the process of visualizing ideas through the following processes: designing, nglowongi, nyumiki, nemboki, coloring, pelorodan, and finishing. This study project produced 12 Batik works with a size of 65 cm x 60 cm which have been processed as finishing, namely on the frame. The twelve batik works are the Rat, Ox, Tiger, Rabbit, Dragon, Snake, Horse, Goat, Monkey, Rooster, Dog, and Pig.